Análisis historiográfico de la reconstrucción de Riobamba tras el terremoto de 1797. - Talahua Luisa, Katherine Gissel (2025)
The present work provides a comprehensive analysis of the impact of the 1797 Riobamba earthquake, focusing on the social, economic, and political consequences of this catastrophe. In this context, the relocation of the city to the Tapi Plain is detailed—a complex process involving prolonged deliberations, conflicts of interest, and technical challenges, such as constructing an irrigation canal to ensure water supply. Additionally, the role of leaders like José Antonio de Lizarzaburu is examined, highlighting his key contributions to the organization and progress of the resettlement. The methodological approach is based on historical research and document analysis, utilizing primary sources such as government and religious archives to understand the earthquake's impact on the region's political, social, and economic life. The study also underscores the transformations triggered by this calamity in Riobamba's urban structure and social dynamics, including material reconstruction and the reorganization of affected communities. In conclusion, the study emphasizes the importance of analyzing historical events such as the 1797 earthquake to understand the past and identify lessons applicable to risk management and natural disaster prevention. The proposed recommendations include strengthening education in risk management, creating public policies that prioritize sustainable reconstruction, and designing early warning systems to protect communities and their cultural heritage.